Spinal Dysraphism Spectrum: A Novel Protocol-based Approach for Accurate Diagnosis on Imaging - Rana, Abhilasha; Krishnan, Venkatram; Jamwal, Rupie (Journal of Pediatric Neurology, 2023)
The spectrum of spinal dysraphism includes various congenital anomalies of the spinal column and spinal cord. Clinical manifestations are varied and range from paraparesis, gastrointestinal, genitourinary, and musculoskeletal anomalies to asymptomatic cases depending on the level and extent of spinal involvement. Magnetic resonance imaging is the gold standard for assessing these complex spinal anomalies. Even for the experienced radiologist, diagnosis can be challenging in complex cases. It is essential to be aware of the normal embryological developmental stages of the spine for an adequate understanding of the complex anatomy, pathogenesis, and cliniconeuroradiological classification of spinal dysraphism, which is necessary for accurately diagnosing each case as a particular pathological entity. In this pictorial essay, we have depicted the stages and process of spinal embryogenesis, cliniconeuroradiological classification, and the imaging spectrum of spinal dysraphism. As the confusing terminologies and the numerous variants can potentially lead to misdiagnosis, we have proposed a step-wise protocol-based imaging approach to analyze each case and arrive at the correct diagnosis systematically. This would be particularly helpful in confusing and difficult cases, as accurate and early diagnosis is crucial for appropriate patient management.
Keywords: spinal dysraphism; magnetic resonance imaging; open spinal dysraphism; closed spinal dysraphism; protocol-based approach